Improved hydrogen production from dry reforming reaction using a catalytic packed-bed membrane reactor with Ni-based catalyst and dense PdAgCu alloy membrane. (30th January 2016) - Sumrunronnasak, Sarocha; Tantayanon, Supawan; Kiatgamolchai, Somchai; Sukonket, Thitinat
Abstract: A catalytic Pd76 Ag19 Cu5 alloy membrane reactor packed with 5% Ni/Ce0.6 Zr0.4 O2 catalyst was adopted in this study to investigate hydrogen production performance from the dry reforming reaction of methane and carbon dioxide. The 1:1 CH4 /CO2 feed was introduced to the reactor with 60 mg of the catalyst at a flow rate of 20 ml/min at 550 °C. The effluent gas compositions were examined using an online gas chromatographer (GC). Compared to a conventional reactor without the membrane, the CH4 and CO2 conversions were significantly increased by 3.5-fold and 1.5-fold, respectively. Correspondingly, the overall H2 yield was greatly improved from about 10–35%. Additionally, the hydrogen selectivity increased from 47 to 53%. It is theorized that the in-situ partial hydrogen withdrawal by the membrane mainly caused the dry reforming reaction equilibrium to shift forward and created a hydrogen-deprived environment unfavorable for the competing reversible water-gas shift reaction to take place. Highlights: PdAgCu alloy membrane was prepared by sequential depositions of Pd, Ag, and Cu onto the substrate. The membrane reactor used consists of 5% Ni/Ce0.6 Zr0.4 O2 catalyst and Pd76 Ag19 Cu5 alloy membrane. The reactor showed improvement in the hydrogen production from dry reforming reaction. The CH4 and CO2 conversions were significantly increased by 3.5 and 1.5 folds, respectively. The hydrogen selectivity was increased from 47 to 53%.